Pre-hospital emergency anaesthesia in the United Kingdom: an observational cohort study. (May 2020) - Turner, Jake; Bourn, Sebastian; Raitt, James; Ley, Erica; O'Meara, Matthew; ,
Abstract: Background: Up to one in eight trauma patients arrive at a hospital with a partially or completely obstructed airway. The UK National Institute for health and Care Excellence (NICE) practice guidelines recommend that trauma patients requiring anaesthesia for definitive airway management receive this care within 45 min of an emergency call, preferably at the incident scene. How frequently this target is achieved remains unclear. We assessed the recorded time to pre-hospital emergency anaesthesia after trauma across UK helicopter emergency medical service (HEMS) units. Methods: We retrospectively recorded time to pre-hospital emergency anaesthesia across all 20 eligible UK HEMS units (comprising 52 enhanced care teams) from April 1, 2017 to March 31, 2018. Times recorded for emergency notification, dispatch, arrival, and neuromuscular blocking agent administration were analysed. Results: HEMS undertook 1755 pre-hospital emergency anaesthetics for trauma across the UK during the study period. There were 1176/1755 (67%) episodes undertaken by helicopter response teams during daylight hours. The median time to pre-hospital emergency anaesthesia was 55 min (inter-quartile range: 45–70); anaesthesia within 45 min of the initial emergency call was achieved in 25% cases. Delayed dispatch time (>9 min) was associated with fewer patients receiving pre-hospital anaesthesia within 45 min (odds ratio: 7.7 [95% confidence intervals: 5.8–10.1]; P <0.0001). Conclusions: The time to achieve pre-hospital emergency anaesthesia by UK HEMS frequently exceeds the recommended 45 min target. Reducing the time to dispatch of emergency medical teams may impact on the delivery of pre-hospital emergency anaesthesia.